Optimising the Conceptualisation of Context; Comment on "Stakeholder Perspectives of Attributes and Features of Context Relevant to Knowledge Translation in Health Settings: A Multi-country Analysis" - Jo Rycroft-Malone; Lisa Rogers; Christopher R. Burton (Kerman University of Medical Sciences, 2022)
Context matters. Therefore, efforts to develop greater conceptual clarity are important for science and practice. In this commentary, we outline some key issues that were prompted by Squires and colleagues' contribution. Specifically, we reinforce context as an interactive concept and therefore something that is hard to 'pin down,' the problematic nature of conceptualising context in implementation and de-implementation, and a requirement for the development of culturally sensitive understandings. Finally, we suggest it is vital that continued investment into providing a more comprehensive list of determinants needs to be accompanied by an equal effort in developing practical methods and tools to support use and application.